Characteristics and value of 'meaningful activity' for people living with dementia in residential aged care facilities: "You're still part of the world, not just existing". (February 2023) - Tierney, Laura; MacAndrew, Margaret; Doherty, Kathleen; Fielding, Elaine; Beattie, Elizabeth
Most residential aged care facilities support residents to participate in activities and the importance of activities that are suited to individual preferences and abilities is widely acknowledged. Participating in activities, including those considered to be 'meaningful' has the potential to improve residents' quality of life. However, what makes activities meaningful for people living with dementia in residential aged care facilities is unclear. The aim of this study was to understand the key characteristics of 'meaningful activity' in residential aged care facilities and the perceived value of residents participating in these activities. Using a qualitative study design, this study explored 'meaningful activities' from the perspectives of people living with dementia in residential aged care facilities, their family members and staff. Across four residential aged care facilities, residents (n = 19) and family members (n = 17) participated in individual interviews while staff (n = 15) participated in focus group interviews. Interviews were recorded, transcribed and analysed using a qualitative content analysis approach. Participant responses suggest that the meaning of an activity is subjective, varying over time and between individuals. Key characteristics of an activity that makes it meaningful include being enjoyable, social and engaging, aligning with the persons' interests, preferences, and abilities. To be considered meaningful, activities need to do more than occupy the person. The activity needs to be linked to a personally relevant goal and an aspect of the individuals' identity. Participating in 'meaningful activities' was perceived as valuable to encourage participation and socialising, provide a sense of normality for residents and improve their wellbeing. The findings of this study further our understanding of the concept of 'meaningful activity' for people living with dementia in residential aged care facilities. Understanding the key attributes of 'meaningful activity' can also provide practical guidance for those supporting people with dementia to participate in these types of activities.